Morphology and Composition of Two Late Wisconsinan Soils Forming in Till and Lacustrine Deposits, Scarborough Bluffs Area, South-Central Ontario - Mahaney, William (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTHalton Till and Glacial Lake Iroquois lacustrine sand and gravel deposits are the major surficial materials exposed at the surface of Scarborough Bluffs in South-Central Ontario. Luvisols formed in these deposits have different morphologies, including depth of weathering, complexity of horizonation, and strength of structural grades which result from parent material differences and pedogenesis. Particle size variations between the two paleosols result, in part, from different modes of deposition, and show that variable amounts of clay were produced pedogenically in the two systems. Clay mineral genesis, involving the transformation of illite and illitesmectite to vermiculite, appears to be restricted to the Iroquois sand paleosol, while some chloritization of illite occurs in both profiles. Changes in the primary mineral contents in the two paleosols suggest a similar magnitude of weathering in both systems. Distributions of vermiculite and dithionite-extractable Fe suggest some preweathering effects in the Halton Till paleosol. Morphological, mineralogical and some soil chemical properties are closely related to the physical attributes of the two different parent materials (till vs lacustrine sand and gravel).